The Role of Roots and Affixes in College English Vocabulary Learning - Fang, Mingdan (Journal of Educational Research and Policies, 2025)
At present, traditional vocabulary learning methods struggle to meet college students’ needs for English vocabulary acquisition and retention. When preparing for College English tests, students are required to memorize a large number of new words. If they still rely on rote memorization, their learning efficiency will be significantly reduced, and their interest in English learning may even be undermined. To explore the feasibility and effectiveness of root-and-affix associative memory and help students memorize words more efficiently, this paper explains how this method enhances college students’ vocabulary retention ability—starting from the definition, characteristics, and application of root-and-affix associative memory—and elaborates on the application and significance of root-based teaching in College English vocabulary instruction. Compared with traditional word-formation teaching, root-based teaching demonstrates greater advantages and feasibility in College English vocabulary teaching.